Addressee as a Factor in Document Type Adaptation - Marina V. Kosova; Mikhail K. Sheptukhin (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The study is devoted to the effectiveness of business communication, provided by a number of intralinguistic and extralinguistic factors. The adaptation process is considered as the creation of a primary document, or a subtype within one type, taking into account the conditions of business communication, and primarily the characteristics of the addressees: their social and legal status; heterogeneity (scope, mass character) or belonging to a certain social group; absence or presence of shared competences; the nature of the information contained in the document and the way it is expressed. The adaptation process is shown to affect the document form, the compositional, substantive and speech organization of its text. Based on the material of two subtypes of the instruction, viewed as an organizational and legal document, which regulates various business processes, the parameters of the document that explicate its adaptation to the characteristics of the addressee are identified and described: the form as a specific implementation of the general document model; the compositional and meaningful structure of the text; speech organization, in particular the use of terminology, modality and speech tonality as a way of formatting the contents. The results obtained complement the available information about the documentary text as an object of linguistics, about the types of adapted texts, and their communicative capabilities.